2018
DOI: 10.1016/j.nbd.2018.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Cocaine-mediated activation of microglia and microglial MeCP2 and BDNF production

Abstract: The molecular substrates underlying cocaine reinforcement and addiction have been studied for decades, with a primary focus on signaling molecules involved in modulation of neuronal communication. Brain-derived neurotrophic factor (BDNF) is an important signaling molecule involved in neuronal dendrite and spine modulation. Methyl CpG binding protein 2 (MeCP2) binds to the promoter region of BDNF to negatively regulate its expression and cocaine can recruit MeCP2 to alter the expression of genes such as BDNF th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 64 publications
3
25
0
1
Order By: Relevance
“…These results are consistent with previous reports that dectin-1 and TLR2 activation modulate macrophage function in the central nervous system and reduce the damaging effects of inflammation ( Dennehy et al, 2008 ; Kelly et al, 2008 ; Lee et al, 2009 ; Gensel et al, 2015 ). Furthermore, these results support previous studies showing that cocaine activates brain microglial cells and that activated microglia-derived EVs play important roles in neuroinflammation and modulation of cell-to-cell communication ( Cotto et al, 2018 ; Periyasamy et al, 2018 ).…”
Section: Resultssupporting
confidence: 91%
“…These results are consistent with previous reports that dectin-1 and TLR2 activation modulate macrophage function in the central nervous system and reduce the damaging effects of inflammation ( Dennehy et al, 2008 ; Kelly et al, 2008 ; Lee et al, 2009 ; Gensel et al, 2015 ). Furthermore, these results support previous studies showing that cocaine activates brain microglial cells and that activated microglia-derived EVs play important roles in neuroinflammation and modulation of cell-to-cell communication ( Cotto et al, 2018 ; Periyasamy et al, 2018 ).…”
Section: Resultssupporting
confidence: 91%
“…A study reported increased levels of MeCP2 in dorsal striatal neurons in rats after cocaine administration [30]. Another study observed that cocaine administration increases MeCP2 expression in hippocampus, frontal cortex, and NAc of rats [31]. Deng et.…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with previous reports that dectin-1 and TLR2 activation modulate macrophage function in the central nervous system and reduce the damaging effects of inflammation (Dennehy et al, 2008;Kelly et al, 2008;Lee et al, 2009;Gensel et al, 2015). Furthermore, these results support previous studies showing that cocaine activates brain microglial cells and that activated microgliaderived EVs play important roles in neuroinflammation and modulation of cell-to-cell communication (Cotto et al, 2018;Periyasamy et al, 2018).…”
Section: Resultssupporting
confidence: 93%